INTERSECTING MEDICAL AND LEGAL RESPONSIBILITIES IN INDONESIA - Komalasari, Rita; Mustafa, Cecep (Indonesia Private Law Review, 2024)
The primary objective of this research is to illuminate the evolution of medical responsibility in Indonesia over time. By examining the complex interplay between law and medicine, social transformations, medical advancements, and shifting legal perspectives, this study seeks to enhance understanding of medical responsibility in Indonesia. Utilizing an interdisciplinary approach grounded in the "Social Construction of Technology" (SCOT) theory, the research employs historical analysis to trace the origins of medical responsibility, its evolution, and the impact of various legal frameworks and cultural shifts in medicine. The study integrates qualitative data from legal and medical sources to provide a comprehensive view. Findings reveal that the evolution of medical responsibility in Indonesia is closely tied to the adoption of, and subsequent resistance to, entrenched notions within medical discourse. The research identifies a trend towards greater judicial independence from traditional medical narratives and an increased willingness to scrutinize established medical practices, particularly in the context of technological advancements. By situating these developments within Indonesia's historical and cultural context, this research enriches the understanding of medical liability's progression and ongoing transformation within a dynamic healthcare landscape. It addresses gaps in existing literature and offers a nuanced perspective on the interaction between law and medicine concerning medical liability.